Chemopreventive effect of the polysaccharides from Grifola frondosa in colitis-associated colorectal cancer by modulating the Wnt/β-catenin/GSK-3β signaling pathway in C57BL/6 mice. (December 2019) - Meng, Meng; Guo, Mingzhu; Wang, Pei; Han, Ran; Zhou, Jiaping; Wang, Chunling
Graphical abstract: Highlights: The polysaccharides from Grifola Frondosa (GFP) caused inhibition of the colon cancer in vivo and in vitro . GFP can inhibit the release of inflammatory factors in high-fat mice. GFP inhibited the viability of tumor by modulating the Wnt/β-catenin/GSK-3β signaling pathway in mice fed with a high-fat diet. Abstract: The aim of this study was to analyze the preventive effect of water-soluble polysaccharides in the maitake mushrooms (Grifola frondosa) fruiting body (GFP) on colon cancer in high-fat (HF) mice and WIDR cells. In vivo, the administration of GFP decreased colon myeloperoxidase (MPO) activity and disease activity index (DAI) compared with HF group ( P  < 0.05), and GFP was significantly inhibited the nitric oxide (NO) while increased of L-Glutathione (GSH) and superoxide dismutase (SOD). The expression of COX-2、IL-6、TNF-α was decreased in GFP -treated group, and the expression of lnterleukin-10(IL-10) and lnterleukin-4(IL-4) was increased. In addition, GFP can regulate the Wnt/β-catenin/GSK-3β signaling pathway to achieve the inhibitory effect on the survival of colon cancer. And CPS-II had high selectivity to tumor cells in vitro . The results revealed that CPS-II can inhibit colon cancer growth in vitro and in vivo, and may be a novel therapeutic agent for the disease.